Clinical relevance of testing for antineutrophil cytoplasm antibodies (ANCA) with a standard indirect immunofluorescence ANCA test in patients with upper or lower respiratory tract symptoms. Issue 3 (March 1994) - Davenport, A; Lock, R J; Wallington, T B
Abstract : BACKGROUND–Reports from specialist nephrological centres have suggested that the antineutrophil cytoplasm antibody (ANCA) test is highly specific and sensitive for patients with Wegener's granulomatosis. To determine the usefulness of the ANCA test in everyday respiratory practice the results of the test were audited in all patients in the south west of England with respiratory symptoms who underwent the test. METHODS–The results of all 335 patients who had presented with upper or lower respiratory tracts symptoms, or both, and were tested for ANCA by the indirect ANCA test in 1990, as recommended in the broadsheet of the British Association of Clinical Pathologists, were audited. Case notes and necropsy reports were available for review in 231 cases (69%), and in the remainder information was obtained by a standard questionnaire. RESULTS–There were 106 positive results, 45 (44%) from patients with Wegener's granulomatosis. The sensitivity and specificity of a positive ANCA test result in this study were 65% and 77% respectively. For a diagnosis of Wegener's granulomatosis the sensitivity and positive predictive accuracy of a positive cytoplasmic ANCA (c-ANCA) test were greater than of a positive perinuclear ANCA (p-ANCA) test. There were 61 positive tests in 266 patients who did not have Wegener's granulomatosis (23%); of these 27 were from patients with infection, 10 with fibrotic lung disease, nine with underlying connective tissue disease, seven with malignancy, and five following pulmonary emboli. Most of these positive ANCA results were p-ANCA (69%) rather than c-ANCA (31%). Serial ANCA requests were made in 15 cases of patients without Wegener's granulomatosis who had an initial positive ANCA test result. In all cases the ANCA tests subsequently became negative. CONCLUSIONS–In this study the sensitivity and specificity of a positive ANCA test result were less than that reported from specialised centres. However, the test was found to be useful in clinical practice, especially c-ANCA, in conjunction with clinical symptoms of respiratory pathology and evidence of renal disease.